1999
DOI: 10.1590/s0100-204x1999000800023
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic fungal (Hyphomycetes) collection: assessment of conidial viability

Abstract: -Twenty four strains of the entomopathogenic fungi (Hyphomycetes) Beauveria bassiana, Metarrhizium anisopliae, Nomuraea rileyi, Paecilomyces farinosus, P. fumosoroseus and P. lilacinus, maintained in the culture collection of Embrapa-Centro Nacional de Pesquisa de Recursos Genéticos e Biotecnologia (Cenargen) and preserved by lyophilization and in liquid nitrogen, had their conidial viability assessed. Germination rates of 16-to 84-month-old cultures stored in liquid nitrogen decreased, on average, less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
1
1
0
1
Order By: Relevance
“…Since in our study dry M. anisopliae spores were plunged into 0.1% tween solution at room temperature (25°C), the drying step of lyophilization might not be the sole source of viability loss. As a matter of fact, imbibitional damage may help explain other poor results previously reported for M. anisopliae spores following freeze-drying (Faria et al, 1999;Horaczek and Viernstein, 2004b). The limited loss of viability observed in our study after fast rehydration of dry B. brongniartii spores suggests that this species is relatively insensitive to imbibitional damage, as previously reported to B. bassiana by Faria and colleagues.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Since in our study dry M. anisopliae spores were plunged into 0.1% tween solution at room temperature (25°C), the drying step of lyophilization might not be the sole source of viability loss. As a matter of fact, imbibitional damage may help explain other poor results previously reported for M. anisopliae spores following freeze-drying (Faria et al, 1999;Horaczek and Viernstein, 2004b). The limited loss of viability observed in our study after fast rehydration of dry B. brongniartii spores suggests that this species is relatively insensitive to imbibitional damage, as previously reported to B. bassiana by Faria and colleagues.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, M. anisopliae was highly sensitive to drying (about 79% loss of viability for unprotected conidia), resulting in 96% viability loss following the whole freeze-drying process. Faria et al (1999) reported viability losses ranging from 23% to 59% for four M. anisopliae isolates following freeze-drying with a mixture of 3% glucose and 3% gelatin as a cryoprotectant, whereas for B. bassiana isolates the loss was in the 2-16% range.…”
Section: Discussionmentioning
confidence: 99%
“…Além de sua importância como fonte de variabilidade genética para seleção de patógenos ou de isolados de patógenos de insetos, o banco de micro-organismos entomopatogênicos é também uma fonte de recursos genéticos utilizados em programas de biotecnologia, melhoramento genético e em outras áreas do conhecimento, proporcionando aos institutos, universidades, empresas e aos que trabalham com micro-organismos entomopatogênicos, material genético a ser aplicado e conservado em longo prazo, devido à sua importância como agente de controle de pragas e até, se for o caso, para uma produção comercial do patógeno (EMBRAPA-CENTRO NACIONAL DE PESQUISA DE RECURSOS GENÉTICOS E BIOTECNOLÓGICOS, 1996). Resultados obtidos por FARIA et al (1999) indicaram que as formas mais eficientes para a preservação de conídios de fungos entomopatogênicos para uma coleção biológica são os métodos de preservação em nitrogênio líquido, onde em média perdeu-se 13,3% da viabilidade conidial após 16 à 84 meses de armazenamento e o método de liofilização, onde após 29 à 49 meses de armazenamento ocorreu uma perda de 28,6 à 94,5% da viabilidade de germinação. Os resultados encontrados confirmam a eficiência dos métodos testados, porém essas técnicas de preservação requerem um alto investimento.…”
Section: Abstract the Making Of An Entomopathogenic Fungal Collection Of Strains Found In Crops And Environmental Preservation Areas In Tunclassified